THE OLDEST VOLCANIC GLASS IN THE EARLY PALEOPROTEROZOIC BONINITE-TYPE LAVAS, KARELIAN CRATON: RESULTS OF INSTRUMENTAL INVESTIGATIONS - Sharkov E.V.; Trubkin N.V.; Krasivskaya I.S.; Bogatikov O.A.; Mokhov A.V.; Chistyakov A.V.; Evseeva K.A.; Zolotykh E.B.; Ladygin V.M. (My University, 2003)
Since Early Precambrian volcanic rocks are typically strongly altered by superimposed processes, they retain primary composition and texture only in exceptional cases. Such a case is observed in the Early Paleoproterozoic volcanic rocks of the Vetrenyi Belt Formation of the synonymous riftogenic structure in southeastern Karelia, where volcanic glass is locally preserved [1-3]. The Sm-Nd, Re-Os, and U-Pb (zircon) ages of volcanic rocks of this formation range from 2.5 Ga in the lower parts to 2.41 Ga in the upper parts of the sequence [1-3]. Zolotykh and Ladygin [4, 5] also confirmed the presence of volcanic glass in these rocks. During short-term field works in 2000, we collected additional samples in the southeastern termination of the graben-shaped Vetrenyi Belt, where the least altered rocks were preserved. The samples were mainly treated at the Institute of Geology of Ore Deposits, Petrography, Mineralogy, and Geochemistry.
Keywords: Paleoproterozoic; Precambrian::Proterozoic::Paleoproterozoic; Докембрий::Протерозой::Палеопротерозойская